Antidiabetic Activity of Eupatorin against Streptozotocin-Induced Diabetes in Rats: Biochemical and Histological Studies - Farasani, Abdullah; Abdelwahab, Siddig Ibrahim (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Diabetes mellitus is a persistent metabolic condition that has emerged as a major public health issue globally. The prevalence of diabetes has been rapidly increasing, posing a major challenge to global healthcare systems. Objectives: The present work was aimed at investigating the anti-diabetic roles of the eupatorin against Streptozotocin (STZ)-induced rat model. Materials and Methods: The rats received 55 mg/kg of STZ to induce diabetes and were then treated with eupatorin for 15 days. At the end of treatments, the blood glucose concentration of experimental rats was evaluated. The biomarkers for renal impairment, including urea and creatinine, serum concentrations of liver marker enzymes, serum levels of lipid profile parameters and oxidative stress markers were assessed with commercial assay kits. The pancreas, liver and kidneys of the rats were subjected to histological studies to assess histological alterations. Results: The current findings demonstrated that eupatorin treatment significantly decreased the blood glucose, urea and creatinine concentrations in the serum of diabetic rats. The eupatorin treatment also reduced the serum concentrations of liver marker enzymes, regulated the lipid profile parameters and mitigated the oxidative stress via up-regulating antioxidants in the rats with STZ-induced diabetes. Moreover, the findings of histological analyses show that eupatorin treatment can protect vital organs from diabetes-induced histopathological alterations in diabetic rats. Conclusion: The current findings indicate that eupatorin may significantly mitigate diabetic conditions and its associated difficulties in STZ-induced rats. Consequently, the current data suggest that eupatorin may serve as an effective therapeutic alternative for diabetes management.
Keywords: Alkaline phosphatase; Eupatorin; Hyperglycemia; Oxidative stress; Triglycerides; Urea